2017
DOI: 10.1136/bmjopen-2017-017604
|View full text |Cite
|
Sign up to set email alerts
|

Do digital innovations for HIV and sexually transmitted infections work? Results from a systematic review (1996-2017)

Abstract: ObjectiveDigital innovations with internet/mobile phones offer a potential cost-saving solution for overburdened health systems with high service delivery costs to improve efficiency of HIV/STI (sexually transmitted infections) control initiatives. However, their overall evidence has not yet been appraised. We evaluated the feasibility and impact of all digital innovations for all HIV/STIs.DesignSystematic review.Setting/participantsAll settings/all participants.InterventionWe classified digital innovations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 124 publications
4
104
0
Order By: Relevance
“…All of these studies were conducted in high-income countries. Daher et al 50 conducted a systematic review and meta-analysis of 99 studies published from 1996 to 2017, and found that SMS interventions improved antiretroviral therapy adherence with pooled odds ratio (OR) of 2.15 (95% confidence interval [CI], 1.18 to 3.91) and clinic attendance rates with pooled OR of 1.76 (95% CI, 1.28 to 2.42). However, the authors did acknowledge that misclassification bias and recall bias were high (58% bias among randomized controlled trials and 64% among quasi-randomized trials) and raised concern regarding the quality of studies included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…All of these studies were conducted in high-income countries. Daher et al 50 conducted a systematic review and meta-analysis of 99 studies published from 1996 to 2017, and found that SMS interventions improved antiretroviral therapy adherence with pooled odds ratio (OR) of 2.15 (95% confidence interval [CI], 1.18 to 3.91) and clinic attendance rates with pooled OR of 1.76 (95% CI, 1.28 to 2.42). However, the authors did acknowledge that misclassification bias and recall bias were high (58% bias among randomized controlled trials and 64% among quasi-randomized trials) and raised concern regarding the quality of studies included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…mHealth strategies, which are described as mobile communications technology used to deliver health care [16], can help surmount issues related to logistics, culture and economics for groups that are either medically or socially marginalized [17]. In the context of HIV care, mHealth strategies have been effective in increasing clinic attendance, treatment adherence and turnaround time from testing to treatment [18]. Furthermore, strategies which utilize mobile technologies for HIV self-testing have been shown to support linkage to care [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, APP-based mHealth interventions have the potential to improve service delivery and positively affect patient outcomes [23]. Smartphones are more portable than computers, and together with their accessibility and intensive daily use by many people, they can enable point-to-point individualised interventions and help reduce some societal and structural barriers faced by stigmatised populations [28]. This study protocol provides a clear and thorough description of an APP-based mHealth intervention and will be used to investigate the effectiveness of mHealth intervention and underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, smartphones are used by 68% of the population in China [24], with up to 97.5% of MSM having a smartphone [25]. Adherence-supporting interventions incorporating mHealth have shown good acceptability and feasibility in HIV-positive MSM [26], and demonstrated efficacy in improving PLWHA's linkage to care, retention in treatment and adherence to ART [27,28]. However, to the authors' knowledge, mHealth interventions to improve the adherence of HIV-positive MSM to ART and potential mechanisms of how an intervention works have not been fully explored in China, and many mHealth interventions have mainly relied on text messages [29].…”
Section: Introductionmentioning
confidence: 99%